Direct transfer of micro-molded electrodes for enhanced mass transport and water management in PEMFC - Deshmukh, Ashvini B.; Kale, Vinayak S.; Dhavale, Vishal M.; Sreekumar, K.; Vijayamohanan, K.; Shelke, Manjusha V. (Electrochemistry Communications, 2010)
Soft lithography technique is used to micropattern the electrodes on the electrolyte membrane of polymer electrolyte fuel cell (PEMFC) in order to alleviate the issues due to poor water management and inadequate reactant distribution in the fuel cell environment. Membrane electrode assembly with the micropatterned electrode has shown an increase in power density at a higher temperature as well as at a higher relative humidity when compared to a flat electrode. Consistency in cell performance is observed in the case of micropatterned electrodes. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Bipolar plate-less PEM fuel cell; Micropatterned electrodes; Microtransfer molding; Soft lithography

High aspect ratio nanoscale multifunctional materials derived from hollow carbon nanofiber by polymer insertion and metal decoration - Balan, Beena K.; Kale, Vinayak S.; Aher, Pradnya P.; Shelke, Manjusha V.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Chemical Communications, 2010)
A novel high aspect ratio material which can simultaneously display multiple functions such as proton and electron conductivity and electrocatalytic activity has been developed by incorporating both platinum nanoparticles and phosphoric acid doped polybenzimidazole along the inner and outer surfaces of a hollow carbon nanofiber.

Template assisted highly ordered novel self assembly of micro-reservoirs and its replication - Hire, Santosh L.; Shelke, Manjusha V.; Kale, Vinayak S.; Galopin, Elisabeth; Kulkarni, Mohan G.; Boukherroub, Rabah; Ogale, Satishchandra B. (Lab on a Chip, 2010)
A novel method is developed for template assisted fabrication of a regular assembly of microcavity arrays. Simple micropatterns on PDMS mold are used to create complex geometries via solvent vapor back pressure in a biodegradable polymer. Cavities are in turn replicated in complimentary PDMS mushroom like microstructures.

Novel catalyst-free synthesis of vertically aligned silicon nanowire-carbon nanotube heterojunction arrays for high performance electron field emitters - Kale, Vinayak S.; Sathe, Bhaskar R.; Kushwaha, Ajay; Aslam, Mohammed; Shelke, Manjusha V. (Chemical Communications, 2011)
A novel, catalyst-free strategy for the direct synthesis of vertically aligned silicon nanowire-carbon nanotube (SiNW-CNT) heterojunction arrays is presented. Such a heterojunction with the junction area in the nanoscale displays enhanced field emission characteristics at low turn-on field, with a nearly three times increase in the field enhancement factor.

Synthesis of silver nanoparticles in an aqueous suspension of graphene oxide sheets and its antimicrobial activity - Das, Manash R.; Sarma, Rupak K.; Saikia, Ratul; Kale, Vinayak S.; Shelke, Manjusha V.; Sengupta, Pinaki (Colloids and Surfaces B-Biointerfaces, 2011)
A solution-based approach to the synthesis of silver (Ag) nanoparticles by chemical reduction of AgNO3 in a graphene oxide (GrO) suspension is demonstrated. X-ray diffraction and transmission electron microscopy indicate that the Ag nanoparticles, of size range 5-25 nm, were decorated on the GrO sheets. The size and shape of the Ag nanoparticles are dependent on the concentration of the AgNO3 solution. Antimicrobial activity of such hybrids materials is investigated against the Gram negative bacteria Escherichia coli and Pseudomonous aeruginosa. The bacterial growth kinetics was monitored in nutrient broth supplemented with the Ag nanoparticle-GrO suspension at different conditions. It was observed that P. aeruginosa is comparatively more sensitive to the Ag nanoparticle-GrO suspension. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Antimicrobial activity; Escherichia coli; graphene oxide; Pseudomonous aeruginosa; Silver nanoparticle